Analysis of V beta 17a expression in new mouse strains bearing the V beta a haplotype (The Rockefeller University Press, 1989)
A set of new mouse strains were produced that carry the V beta a haplotype of the TCR-alpha/beta and any of a number of different H-2 haplotypes on backgrounds derived from related C57BL, C57L, and C57BR mice. Study of V beta 17a expression in these mice confirms the association between the presence of IE and the deletion of V beta 17a+ T cells. A second H-2 gene causing deletion of V beta 17a+ T cells was mapped in these mice to the K end of H-2k, and H-2 influences on the level of selection of CD4+ V beta 17a+ T cells were indicated.